Impact of Indolent Inflammation on Neonatal Hypoxic-Ischemic Brain Injury in Mice - Barks, John D. E. (2007)
This report describes a new experimental model to evaluate the effect of a recurrent systemic inflammatory challenge, after cerebral hypoxia-ischemia in immature mice, on the progression of brain injury. Treatment with a low dose of lipopolysaccharide (E. coli O55:B5, 0.2 mg/kg for 3 days, then 0.1 mg/kg for 2 days) daily for 5 days after unilateral cerebral hypoxia-ischemia (right carotid ligation followed by 35 min in 10% O(2)) in 10-day-old mice resulted in increased right forebrain tissue damage (35.6% reduction in right hemisphere volume compared to 20.6% reduction in saline-injected controls), in bilateral reductions in corpus callosum area (by 12%) and myelin basic protein immunostaining (by 19%), and in suppression of injury-related right subventricular zone cellular proliferation. The post-hypoxic-ischemic lipopolysaccharide regimen that amplified brain injury was not associated with increased mortality, nor with changes in body temperature, weight gain or blood glucose concentrations. The results of the present study demonstrate that systemic inflammation influences the evolution of tissue injury after neonatal cerebral hypoxia-ischemia and may also impair potential recovery mechanisms.